2010
DOI: 10.1007/bf03353629
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy electronic states of carbon nanocones in an electric field

Abstract: The low-energy electronic states and energy gaps of carbon nanocones in an electric field are studied using a single-S-band tight-binding model. The analysis considers five perfect carbon nanocones with disclination angles of 60°, 120°, 180°, 240° and 300°, respectively. The numerical results reveal that the low-energy electronic states and energy gaps of a carbon nanocones are highly sensitive to its geometric shape (i.e. the disclination angle and height), and to the direction and magnitude of an electric fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…To minimise computation time, the nearest-neighbour tight binding approximation is commonly used to determine the energy states and overlap is ignored. This assumption has also been used for calculating the energy states of other carbon-based materials such as carbon nanotubes [ 8 ] and carbon nanocones [ 9 ]. Recently, Reich et al [ 10 ] have demonstrated that this approximation is only valid close to the K points, and a tight binding approach including up to third nearest-neighbours gives a better approximation to the energy dispersion over the entire Brillouin zone.…”
Section: Introductionmentioning
confidence: 99%
“…To minimise computation time, the nearest-neighbour tight binding approximation is commonly used to determine the energy states and overlap is ignored. This assumption has also been used for calculating the energy states of other carbon-based materials such as carbon nanotubes [ 8 ] and carbon nanocones [ 9 ]. Recently, Reich et al [ 10 ] have demonstrated that this approximation is only valid close to the K points, and a tight binding approach including up to third nearest-neighbours gives a better approximation to the energy dispersion over the entire Brillouin zone.…”
Section: Introductionmentioning
confidence: 99%
“…( 25)-( 29) are substituted into Eqs. ( 18)-( 23): (49) We presuppose that the following expression may be expressed in terms of an exponential displacement field:…”
Section: Motion Equations Of the Nanoplates With Stretching Effectmentioning
confidence: 99%
“…Furthermore, the presence of electric fields near nanostructures can substantially enhance the emission properties of spontaneous emitters due to the intensified electric field strength [48]. Moreover, electric fields can induce changes in the electronic properties of nanostructures, such as adjusting state energies, energy gaps, and Fermi levels, thereby influencing their natural frequencies [49]. The adjustability of electronic transport in nanowires by transverse electric fields further underscores the impact of electric fields on the vibrational characteristics of nanostructures [50].…”
Section: Introductionmentioning
confidence: 99%
“…Optical absorption measurements provide information about the electronic dispersion in nanomaterials due to the optical excitations are sensitive to the geometrical and topological characteristic of the systems [36,37]. On other hand, external electric and magnetic fields have been largely used as a common tool to modulate a large number of interesting physical properties in carbon-based nanostructures [38][39][40][41][42]. In particular, the presence of electric field can be considered by submitting the nanostructure to opposite charged capacitor plates, generating a controlled electric field.…”
Section: Introductionmentioning
confidence: 99%